THE INFLUENCE OF SEGMENTING, TARGETING, AND POSITIONING ON CONSUMER PURCHASE DECISIONS AT MALIKA BAKERY & CAKE SHOP IN LHOKSEUMAWE CITY - Saleha; T. Edyansyah; Sapna Biby; Muchsin (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Segmenting, Targeting, and Positioning (STP) on consumer purchase decisions at Malika Bakery & Cake Shop in Lhokseumawe City. A quantitative approach with a survey method was employed, using structured questionnaires distributed to 115 respondents selected through purposive sampling. The collected data were analyzed using multiple linear regression with the help of SPSS software. The results show that all three independent variables—Segmenting, Targeting, and Positioning—have a positive and significant influence on purchase decisions, both partially and simultaneously. The coefficient of determination (R²) value of 55.2% indicates that consumer purchase decisions are largely influenced by the STP model, while the remaining 44.8% is explained by other external factors. These findings confirm that an effective implementation of STP strategies can enhance consumer interest and loyalty and serve as a strategic reference for MSMEs in developing more targeted marketing efforts.